Successional variation in carbon content and wood specific gravity of four tropical tree species - Navarro, Marcela; Moya, Róger; Chazdon, Robin; Ortiz, Edgar; Vilchez, Braulio (Bosque (Valdivia), 2017)
The carbon content and the specific gravity of wood are indirect indicators of carbon storage capacity of trees. We monitored carbon content in four tropical species (Apeiba tibourbou, Guatteria amplifolia, Hyeronima alchorneoides and Tetrathylacium macrophyllum) in four different succession stages (5-15 years, 15-30 years, 30-50 years and old-growth forest of approximately 80 years old) in humid lowland forests in Costa Rica's Osa Peninsula. Carbon content varied significantly, from 0.41 to 0.51, across species and across successional stages, but it was not affected by diameter at breast height in any species. Mean wood specific gravity varied 3-fold across species, from 0.18 (A. amplifolia) to 0.54 (H. alchorneoides), whereas carbon content ranged from 0.40 (A. amplifolia) to 0.51 (H. alchorneoides). Specific gravity varied significantly (from 0.41 to 0.55) across successional stages only in G. amplifolia, whereas carbon content was different in some successional stages in A. tibourbou, H. alchorneoides and T. macrophyllum. Specific gravity and carbon content were correlated only in T. macrophyllum. Finally, results suggest that carbon content pertains to each species and it is affected by the succession stage.